Arbutus unedo leaf extracts as potential dairy preservatives: case study on quark cheese. Issue 9 (27th April 2022) - Derbassi, Nabila; C. Pedrosa, Mariana; Heleno, Sandrina; Fernandes, Filipa; Dias, Maria Inês; Calhelha, Ricardo C.; Rodrigues, Paula; Carocho, Marcio; Ferreira, Isabel C. F. R.; Barros, Lillian
Abstract : The plant kingdom is an endless source of molecules that can be applied in almost all realms of society. Abstract : The plant kingdom is an endless source of molecules that can be applied in almost all realms of society. The food industry has profited from the use of plants and their derived materials for many decades. Recently, the food industry has been looking into plants to find different ways of either preserving, coloring or sweetening foods. In this work, leaf extracts of Arbutus unedo L. obtained by dynamic maceration and ultrasound assisted extraction with prior optimization of their extraction conditions through the response-surface methodology, were incorporated in quark cheese as natural preservatives and analyzed over 8 days of shelf-life. Both extracts showed antioxidant activity with no toxicity towards primary cell lines at the maximum tested concentration, as well as antibacterial activity, especially against Gram-positive strains. After their incorporation in quark cheese, no significant changes were observed in the nutritional profile and physical traits of the quark cheeses, while the microbial load was highly reduced in the cheese, especially using the extracts obtained from dynamic maceration. Thus, leaf extracts of A. unedo can be promising candidates for use in the food industry as natural preservatives.